Phenolic compounds from different bryophyte species and cell compartments respond specifically to ultraviolet radiation, but not particularly quickly - Soriano, Gonzalo (Plant physiology and biochemistry : PPB, 2019)
Copyright © 2018 Elsevier Masson SAS. All rights reserved.